use the product rule
y' = (1)(x^2+5) + (x-3)(2x) = 3x^2 - 6x+ 5
Differentiate (x-3) (x^2+5) with respect to x
2 answers
OR
( x - 3 ) ( x² + 5 ) = x² ∙ x - x² ∙ 3 + 5 ∙ x - 5 ∙ 3
( x - 3 ) ( x² + 5 ) = x³ - 3 x² + 5 x - 15
d / dx ( x³ - 3 x² + 5 x - 15 ) = 3 x² - 3 ∙ 2 x + 5
d / dx ( x³ - 3 x² + 5 x - 15 ) = 3 x² - 6 x + 5
( x - 3 ) ( x² + 5 ) = x² ∙ x - x² ∙ 3 + 5 ∙ x - 5 ∙ 3
( x - 3 ) ( x² + 5 ) = x³ - 3 x² + 5 x - 15
d / dx ( x³ - 3 x² + 5 x - 15 ) = 3 x² - 3 ∙ 2 x + 5
d / dx ( x³ - 3 x² + 5 x - 15 ) = 3 x² - 6 x + 5